PEMBUATAN ALAT PENGERING SURYA UNTUK HASIL PERTANIAN MENGGUNAKAN KOLEKTOR BERPENUTUP PRISMA SEGITIGA - Salomo -; M. Ginting; R. Akbar (Jurnal APTEK, 2013)
Has made solar dryers for drying cassava and bananas, cassava sliced crosswise and bananas sliced lengwise with the same thickness, which is 2 mm. In this study covered a triangular prism collector connected to the drying chamber.